Fractionated alpha and mixed beam radiation promote stronger pro-inflammatory effects compared to acute exposure and trigger phagocytosis - Karimi Roshan, Mostafa; Belikov, Sergey; Ix, Melissa; Protti, Nicoletta; Balducci, Claudia; Dodel, Richard; Ross, J. Alexander; Lundholm, Lovisa (Frontiers in Cellular Neuroscience, 2024)
Aiming to evaluate safety aspects of a recently proposed approach to target Alzheimer's disease, we mimicked a complex boron neutron capture therapy field using a mixed beam consisting of high-and low-linear energy transfer (LET) radiation, 241 Am alpha particles (α) and/or X-ray radiation respectively, in human microglial (HMC3) cells. Acute exposure to 2 Gy X-rays induced the strongest response in the formation of γH2AX foci 30 min post irradiation, while αand mixed beaminduced damage (α:X-ray = 3:1) sustained longer. Fractionation of the same total dose (0.4 Gy daily) induced a similar number of γH2AX foci as after acute radiation, however, αor mixed irradiation caused a higher expression of DNA damage response genes CDKN1A and MDM2 24 hrs after the last fraction, as well as a stronger decrease in cell viability and clonogenic survival compared to acute exposure. Phosphorylation of STING, followed by phosphorylation of NF-κB subunit p65, was rapidly induced (1 or 3 h, respectively) after the last fraction by all radiation qualities. This led to IL-1β secretion into the medium, strongly elevated expression of pro-inflammatory cytokine genes and enhanced phagocytosis after fractionated exposure to αand mixed beam-irradiation compared to their acute counterparts 24 hrs post-irradiation. Nevertheless, all inflammatory changes were returning to basal levels or below 10-14 days post irradiation. In conclusion, we demonstrate strong transient pro-inflammatory induction by daily high-LET radiation in a microglia model, triggering phagocytosis which may aid in clearing amyloid beta, but importantly, from a safety perspective, without long-term alterations.